How Convenience, Price, Store Layout and Technology Influence Buying Behavior of Different Millennial Groups in the Convenience Stores in Vietnam - Thao, Dam Thi Phuong (H. : ĐHQGHN, 2020)
It is undeniable that convenience stores have expanded rapidly in the Vietnam retail market in recent years [1]. Convenience store chains such as Circle K, 7-Eleven, VinMart and B’s Mart have been popular grocery shopping destinations for shoppers in Vietnam because of the busy modern life and the restricted time for shopping. Noticeably, Millennials with tremendous spending power have become an important shopper group of the convenience store. This research analyses the buying behavior of Millennials and the influential levels of factors including convenience, store layout, price and technology on different Millennial groups in this market.